Nonprofit Hospital CEO Compensation: Does Quality Matter? - Jenkins, Derek; Short, Marah; Ho, Vivian (Medical care, 2025)
Past research has documented that increases in profits and health system size, as well as increases in the reward generosity for improving these metrics play an important role in explaining increases in nonprofit hospital CEO pay between 2012 and 2019. To test whether hospital quality measures play a supplemental role in determining CEO pay. We estimated linear regressions for 2012 and 2019 of the log of CEO wages on system or independent hospital characteristics, including quality. The regressions were used to construct a Oaxaca decomposition of factors associated with CEO compensation. One thousand forty-seven nonprofit health systems and independent hospitals in 2012 and 812 in 2019. CEO compensation, hospital profits, charity care, hospital size, teaching status, system status, 30-day mortality rate for pneumonia patients, hospital-wide 30-day readmission rate. We find that better quality was more closely associated with higher pay among hospital CEOs in 2012 versus 2019. The inclusion of these quality measures in the analysis somewhat reduced the observed relative return for leading larger hospitals or health systems in 2012, but not in 2019. The link between quality and CEO pay is weaker in 2019 than in 2012. The results suggest that nonprofit hospital CEOs are being rewarded more for leading large hospitals or systems, but not for providing higher quality care.